2022
DOI: 10.2147/ppa.s358952
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Use and Predictors of Use of Maternity Waiting Home among Pregnant Women in Hargeisa City Health Centers, Somaliland

Abstract: Background Maternity waiting homes (MWHs) can help women receive the necessary obstetric care and referral if needed. However, there is a lack of evidence on whether women have the desire to stay away from their homes and the sociocultural predictors of their decision in Somaliland. Objective The purpose of this study was to measure predictors of the intention of women to stay in MWHs using the theory of planned behavior in Hargeisa city, Somaliland. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This might imply that those who have some formal schooling may have less concerns to the MWH services or were not using MWHs. This is consistent with findings from a study in Ethiopia 31 whereas it contrasts with a study from Somaliland 36 . Further studies are needed to justify why having no or lower educational status was found to be associated with the knowledge of MWHs.…”
Section: Discussionsupporting
confidence: 90%
“…This might imply that those who have some formal schooling may have less concerns to the MWH services or were not using MWHs. This is consistent with findings from a study in Ethiopia 31 whereas it contrasts with a study from Somaliland 36 . Further studies are needed to justify why having no or lower educational status was found to be associated with the knowledge of MWHs.…”
Section: Discussionsupporting
confidence: 90%